VARIASI GENETIK, HERITABILITAS, TINDAK GEN DAN KEMAJUAN GENETIK KEDELAI (Glycine max Merrill) PADA ULTISOL - Suprapto Suprapto; Narimah Md Kairudin (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
Information on genetic variation, heritability, gene action and genetic advance were important in the development of soybean varieties adapted on Ultisol. The objective of this experiment was to estimate genetic variation, hertability, gene action and genetic advance from the populaton used in breeding program. Six genotypes, i.e Dempo, Cikuray, Davros, Orba, Sindoro and Wilis were intercrossed using diallel Griffings’ Method 2 Model 1 (1956). These six genotypes and 15 F1  hybrids were planted on Ultisol using randomized complete block design with three replications located in Medan Baru village, Bengkulu city in 1999. The results of this experiment revealed that all traits showed low to high genetic variation, high broadsense heritability, low to high narrowsense heritability and genetic advance. Date of flowering and root length were fully controlled by additive gene action, however harvest index was fully controlled by   negative dominant gene action and epistasis. Other traits were controlled by positive and negative partially dominant, and positive overdominant  genes.